2008
DOI: 10.1111/j.1442-2050.2008.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Long beneficial effects after lipo-prostaglandin E1 administration on the ischemic gastric tube in pigs

Abstract: Lipo-prostaglandin E1 (PGE1) is a new preparation of PGE1 in which it is bound to lipids in order to slow PGE1 release and delay its rate of metabolism. We investigated how long the beneficial effects of intravenous administration of lipo-PGE1 on the ischemic gastric tube continue. The gastric tube was constructed using 15 domestic pigs under general anesthesia and saline, unmodified PGE1 and lipo-PGE1 were infused continuously at a rate of 0.05 microg/kg/min for 10 minutes. Tissue blood flow (TBF) was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In an experimental study in pigs, significant improvement in gastric tube blood flow was found following intravenous administration of unmodified prostaglandin E 1 (PGE1) and lipo-PGE1 (p<0.01). 18 In a study of gastric ischaemic preconditioning, Beck et al showed in animal models that if the short gastric and left gastric vessels were ligated three weeks prior to oesophagectomy, formation of the gastric tube resulted in the gastric blood flow falling to only 60% of the baseline compared with 16% in those who were not preconditioned (p=0.07). 19 Hölscher et al described their study of 83 cases where laparoscopic preconditioning of the stomach was undertaken at an average of 4.3 days prior to the definitive procedure.…”
mentioning
confidence: 99%
“…In an experimental study in pigs, significant improvement in gastric tube blood flow was found following intravenous administration of unmodified prostaglandin E 1 (PGE1) and lipo-PGE1 (p<0.01). 18 In a study of gastric ischaemic preconditioning, Beck et al showed in animal models that if the short gastric and left gastric vessels were ligated three weeks prior to oesophagectomy, formation of the gastric tube resulted in the gastric blood flow falling to only 60% of the baseline compared with 16% in those who were not preconditioned (p=0.07). 19 Hölscher et al described their study of 83 cases where laparoscopic preconditioning of the stomach was undertaken at an average of 4.3 days prior to the definitive procedure.…”
mentioning
confidence: 99%